Structured discharge procedure for children admitted to hospital with acute asthma: a randomised controlled trial of nursing practice. Issue 2 (1st February 1999) - Wesseldine, L J; McCarthy, P; Silverman, M
Abstract : BACKGROUND: Discharge planning is becoming an important part of the management of childhood asthma in hospital. Readmission to hospital, although often inevitable, might represent a failure of the opportunity for intervention presented by a brief period of supervised care in hospital. AIM: To examine the impact of a structured, nurse-led discharge package for children admitted to hospital with acute asthma on readmission to hospital, reattendance at the accident and emergency (A&E) department, and general practitioner consultations for asthma. METHODS: A structured nurse-led discharge package, consisting of a 20 minute patient education programme and self management plan for children with asthma was developed on the wards of a busy children's hospital. A randomised controlled trial was conducted involving 160 children aged 2–16 years admitted for asthma over a 12 month period. Readmission and A&E reattendance's over the six months after discharge from hospital were obtained from the hospital computerised information system and general practitioner consultations from practice records. RESULTS: Children in the intervention group were significantly less likely to be readmitted to hospital in the next six months than those in the control group (12 of 80 v 30 of 80 patients), and significantly less likely to attend the A&E department (6 of 80 v 31 of 80). Significantly fewer children in the intervention group had visits to their general practitioner for problematic asthma (31 of 78 v 72 of 77 for whom data were available). CONCLUSION: By delivering the simplest form of education and support during a child's stay in hospital, readmissions over a six month period were reduced. The programme was designed to be suitable for administration by nursing staff on the children's wards after a brief period of training.